(untitled) - Worrall, Jonathan (Hoboken, N.J., 2007)
From Wall Street to the Great Wall shows you how to safely invest in the expanding Chinese economy. Filled with in-depth insight and expert advice, this book provides you with a step-by-step template on how to cut across cultural, language, and geographical barriers and identify potential investment opportunities in one of the hottest markets in the world.
Keywords: Investments; China